South Africa's voluntary relinquishment of its nuclear arsenal and accession to the Treaty on the Non-Proliferation of Nuclear Weapons in terms of international law - Heald, Geoffrey Ronald (My University, 2011)
The subject of this research is “South Africa’s Voluntary Relinquishment of its Nuclear Arsenal and Accession to the Treaty on the Non-Proliferation of Nuclear Weapons in Terms of International Law”. The research found that international law considerations did indeed play an important role in guiding South Africa’s relinquishment of its nuclear arsenal, and in accession to the NPT. The dissertation was conducted by interviewing an expert sample of the key persons who were actually involved with, and led, South Africa’s relinquishment of its nuclear arsenal and accession to the Treaty on the Non-Proliferation of Nuclear Weapons. The decision to interview the expert respondents was followed in order to understand the respondents’ animus or state of mind, and the logos of the decision to relinquish the nuclear weapons and accede to the NPT. The study sample included: • Mr FW de Klerk, former President of South Africa, who instructed that the nuclear arsenal should be relinquished, and that South Africa should accede to the NPT; • Professor Wynand Mouton, whom Mr de Klerk appointed as the Oversight Auditor of South Africa’s nuclear relinquishment and its accession to the NPT; • Professor Waldo Stumpf, who successfully project-managed the nuclear relinquishment process, and brought accession to the NPT into reality; • Mr Pik Botha, who was South Africa’s longest-serving Minister of Foreign Affairs, and who later held the portfolio of Minister of Energy. Mr Botha was personally involved in leading many important international negotiations that pertained to South Africa’s nuclear status over some decades; and • Dr Neil Barnard, who was Director of South Africa’s National Intelligence Service at the time. An important and new research finding was that all of the respondents indicated that the reason the nuclear weapons were relinquished and South Africa acceded to the NPT was that the relinquishment of these weapons and the accession to the NPT were symbiotically interconnected with the constitutional settlement in South Africa. For the respondents, it was a causa sine qua non of the international acceptance and recognition of South Africa’s non-racial constitutional settlement. The respondents were ad idem that it would have been well-nigh impossible to have achieved a peaceful constitutional settlement which was internationally 5 legitimate without relinquishing these weapons and acceding to the NPT prior to the conclusion of the constitutional negotiations. Had South Africa held onto this nuclear arsenal, it would have created international mistrust, because it would have begged the question (petitio principii): “What is the purpose of their retention?” The perpetuation of the nuclear weapons programme would have created international doubt as to the sincerity of the constitutional transition and contributed to the continued recognition of South Africa as a pariah state. This finding has not been reported in the literature and is therefore a new contribution to knowledge about South Africa’s constitutional transition. Although not publicly visible, the relinquishment of the nuclear arsenal and South Africa’s accession to the NPT were purposively linked, and indeed synchronised, with the constantly changing status of the constitutional negotiations – ratione temporis. The link between the relinquishment of the nuclear arsenal and the accession to the NPT was purposefully kept secret. This was because it was reasoned that the matter of South Africa’s design of a nuclear arsenal, its possession of these weapons, its dismantlement of these weapons, and its accession to the NPT formed such a potentially contentious matter, both nationally and internationally, that it could easily have thrust the entire constitutional transition into jeopardy. For this reason it was decided (wisely, in the researcher’s view) to address the matter of relinquishment and accession to the NPT in camera. It was conducted in camera because the security of the state was at stake. The testimony of the respondents made it clear that this subject was sufficiently incendiary to have derailed the constitutional negotiations and settlement, and plunged the country into chaos. The research discovered that the reason the decision was reached to relinquish the nuclear arsenal and accede to the NPT was to ensure that South Africa was recognised as a constitutional democracy and a respected member of the international community of nations. The mission was conducted in order to achieve state succession in a stable framework of constitutional continuity. The research also discovered that a number of the countries that have relinquished their nuclear weapons and acceded to the Treaty on the Non- Proliferation of Nuclear Weapons did so because of the imperative to create a positive state recognition status amongst the international community. Had South Africa retained the nuclear arsenal during the constitutional negotiations, and afterwards, it would have tainted and jeopardised the state succession and the constitutional continuity of the country. It would have endowed the government-in-waiting with a poisoned chalice and undermined Mr Mandela’s stature as a leader. The decision was made by Mr de Klerk and conducted in good faith insofar as all stakeholders were concerned. Comity was displayed by the National Party towards the African National Congress – the regime-in-waiting – in order to endow it with the opportunity of becoming a successful government. The research found that Mr de Klerk, together with his team, carefully reconciled and harmonised South African municipal law with international law in order to obviate a conflict of laws. This harmonisation of law was important in establishing respectful relationships and comity with the International Atomic Energy Agency, which is an organ imbued with international legal personality under the United Nations Charter, and with the international inspectors, including those from inter alia the United States, Russia, the United Kingdom, China and France. The expert respondents were all in consensus that South Africa could never have lawfully deployed the nuclear weapons in any conceivable military conflict, including in the case where the very existence of the South African State might have been at risk. They unanimously expressed the opinion that such usage would have constituted a mala in se and been contrary to natural law and peremptory norms of humanity. The principles of jus cogens and erga omnes permeated their assessment of the legality of any usage of nuclear weapons. The respondents were also in agreement that any actual use of these weapons would be disproportionate, indiscriminate, escalatory, and would not be able to discern friend from foe, and therefore would be contrary to international humanitarian law. The usage of a nuclear bomb would have been a threat to world peace in terms of the United Nations Charter, which might have justified a United Nations-sanctioned military invasion of South Africa to counteract such a threat to world peace, as was the case when Iraq invaded Kuwait. The interviewees were in consensus that if the nuclear weapons had been deployed, they would have escalated conflict, and created an international reprisal risk with potentially disastrous consequences for South Africa, the region, and indeed for the world at large. The research sample further indicated that any operational use of these nuclear weapons would have created disproportional consequences, which would, by deduction, have contravened inter alia: the Geneva Conventions, the Hague Regulations Conventions, the Kellogg–Briand Pact (1928), the Martens Clause, and therefore international humanitarian law. It would have raised the question of state responsibility for wrongful actions, which would also have included contraventions of international environmental law caused by trans-boundary nuclear pollution. Individuals committing wrongful actions could not have pleaded immunity from such wrongfulness by claiming immunity under South African municipal law. The respondents subscribed to a positive law interpretation of the legality of nuclear deterrence, which is the position that the Nuclear Weapons States have assumed. In its essence, this positive law view subscribes to the principle contained in the Lotus case, that what is not prohibited ispermitted. Natural law and positive law have oppositional reasoning as regards the legality of nuclear weapons, and this logical tension was evident in the research. The respondents revealed a difference of opinion as far as their understanding of the legality of the development, possession, testing and deterrence versus actual usage of nuclear weapons is concerned. They were of the view that any military usage or nuclear test would be illegal, but regarded the development, possession and deterrent usage of nuclear weapons as being lawful. The relinquishment process and accession to the NPT was conducted as a secret set of negotiations contiguous with the constitutional negotiations. It is a fact that the African National Congress was not informed about these negotiations until Mr de Klerk issued his formal announcement about the relinquishment and accession to the NPT on 23 March 1993. Mr Mandela was therefore presented with the reality of relinquishment and accession as a fait accompli. South Africa’s rollback is compared with the relinquishment process in Iraq in an attempt to discover whether insight and knowledge from the South African case might be transferred and applied to other countries that are contemplating the same actions. The provisional answer to this question is that partial aspects of the knowledge that was created in South Africa might possibly constitute elements of precedent. The application and transference of this knowledge would always need to be tailored to the unique context, facts and circumstances that might prevail in the transferee state in question. Most certainly all nuclear relinquishment and accession processes need to be conducted as extremely serious projects and in good faith.
Keywords: Nuclear weapons; South Africa; International law